Sulla pace e sul nesso fra etica e politica in Kant e Jaspers - Costanzo, Giovanna (B@belonline, 2024)
In a time in which conflicts and acts of cruelty and inhumanity towards the civilian population are intensifying, it appears evident that those who govern are less and less capable of building paths to peace. If this request does not become a priority, the international community risks weakening. Immanuel Kant understood this well when in 1795, faced with a warlike Europe, he asked himself how peace could be guaranteed and, above all, what tools a politician should equip himself with to govern well. At the end of the Second World War and faced with the fear of a possible atomic war, Karl Jaspers well understood the relevance of Kant’s lesson: surrendering to a horizon of war always creates alibi for surrendering to the threats of new and more fearsome dictators, which instead must be contrasted.